DEVELOPMENT OF A MICROABRASIVE FREE ROTATING SPHERE TEST RIG FOR THE EVALUATION OF HARDFACING DEPOSITS - López Escobar, Iván P.; Ortiz Méndez, Tamara M.; Cruz Crespo, Amado (Centro Azúcar Journal, 2022)
Introduction: In the last decades, the use of the microabrasive rotating sphere test method has been extended in the evaluation of ferrous materials, given its technical-economic advantages, as well as its facilities in the evaluation of hardfacing deposits. Objetive: To develop a free rotating sphere microabrasive testing equipment for the characterization of metallic materials and hardfacing deposits, using design solutions that allow its economic manufacture. Materials and methods: The "Autodesk Inventor Professional 2014" software was used for the design of the equipment, as well as in the modeling of the loads and displacements of the elements of the assembly. Construction steels, carbon steels and an aluminum alloy were used for the fabrication. The parts were manufactured by machining, heat treatment and welding. The adjustment of the equipment was carried out by means of a circularity study of the footprints. Results and Discussion: The developed equipment meets the requirements of the microabrasive wear test. The wear traces obtained on heat-treated GOST X12M steel showed circularity and sharpness of contour, which proves the rigidity of the equipment. This allows its use in the evaluation of metallic materials and hardfacing deposits of high hardness. Conclusions: The developed equipment presents a simple configuration, the mechanical stresses in its components are relatively low, which allows its design with materials of low mechanical resistance. The traces obtained in the adjustment tests show adequate circularity and contour definition, indicating the absence of vibrations that affect the results.